Alligators in the Sewers: Urban Legends about Terrifying Animals and Frightening Places - Mikos, Éva (Ethnographica et Folkloristica Carpathica, 2022)
The aim of the present study is to provide an overall picture of the nature of urban folklore using the “Alligators in the Sewers” urban legend type circulated in both the Hungarian and international press and by word of mouth. While contemporary legends have attracted only sporadic attention in Hungarian research to date, by illustrating the historical development of this legend type the aim of the present case study is to demonstrate how the phenomenon has existed in the Hungarian press for almost 200 years.The present study attempts to identify the kind of opportunities for interpretation offered by these stories in the field of folkloristics; the extent to which they are relevant beyond their literal meaning; and the ways in which they shed light on modern-day understandings of the world. Giant reptiles that are not indigenous to Europe are terrifying to the average individual, while at the same time they evoke a yearning for the natural world in city dwellers trapped amid concrete walls. Urban sewers and storm drains hold similar terrors: on the one hand, they are there to remove filth and symbolize the more unsavory aspects of urban life, while on the other hand their hidden presence beneath the ground offers ample opportunity for the projection of numerous fantasies. Animals that lurk in the sewers, from where they emerge to attack people, are manifestations, contained within simple, traditional narrative frameworks, of the murkiness of highly structured societies and of the sense of danger that this opacity engenders in us. The emergence and persistence of such stories can be attributed to a number of social practices, such as circuses, sideshows, and the keeping of reptiles as pets, along with the respective press reports and rumors.